Collaborative Governance Strategies For Community-Based Tourism Village Development To Increase Local Revenue - Widiya Puspita Rani; Ricko Rivalldo Gustiar; Muhammad Ilham Mulyadi; Mukarto Siswoyo; Sri Wulandari (PT Publikasiku Academic Solution, 2024)
The development of Cibuntu Tourism Village will grow if there is participation from stakeholders between the government, the community, and the private sector in providing public services in the tourism sector such as infrastructure, roads, facilities, and promotion. Collaborative governance is an effective strategy to develop Cibuntu Tourism Village given the limited budget from the government. This research aims to explore the collaboration between the government, the community, and the private sector in developing Cibuntu Tourism Village and improving the economy of the local community and the Regional Original Revenue of Kuningan Regency. This research uses a qualitative method through a descriptive approach by taking the research location in Cibuntu Tourism Village, and the Kuningan Regency Youth, Sports and Tourism Office as a supporting location. The data collection techniques used are literature study, observation, interviews, and documentation. The results of this study use the theory of Ansell and Gash (Astuti et al., 2020) which includes setting initial conditions, institutional design, leadership, and collaborative processes. In Ansell and Gash's theory, the leadership indicator is not optimal due to the lack of communication and cooperation between the Cibuntu Village government and the Kuningan Regency Youth, Sports, and Tourism Office. This research also identified supporting and inhibiting factors in the development of Cibuntu Tourism Village. Supporting factors include cultural potential, beautiful nature, socio-historical aspects, and agriculture and livestock. The inhibiting factors include lack of coordination, access far from the main road, lack of digital promotion, and inadequate human resources. The development of Cibuntu Tourism Village through Collaborative Governance can improve the economy of the local community and the Original Revenue of Kuningan Regency. However, to achieve optimal results, it is necessary to improve communication and cooperation between the village government and related agencies, as well as increase digital promotion and human resource development. Identification and utilization of local potential is also the key to success in the development of this tourism village.